KNOWLEDGE AND AWARENESS ON COMPUTER VISION SYNDROME (CVS) AND THEIR CONTRIBUTING FACTOR AMONG UNDERGRADUATE UNIVERSITY STUDENTS - Zainul Azlan, Nurhazirah; Kamaruddin, Amalia; Othman, Noratikah; Md. Isa, Muhammad Lokman (Malaysian Journal of Public Health Medicine, 2024)
The surge in the use of digitization in daily life has led to a condition known as computer vision syndrome (CVS), which is at risk of becoming a major health issue involving the vision and musculoskeletal systems. Thus, this study will determine the level of knowledge and awareness of CVS among International Islamic University Malaysia (IIUM) Kuantan students. A quantitative cross-sectional study with convenience sampling was conducted among 216 undergraduate students at the IIUM Kuantan Campus from October to November 2021. Around 79.2% of respondents never heard of the term CVS. The majority of the respondents use mobile phones (52.3%) compared to other digital devices and spend more than 3 hours in front of the screen per day (48.6%). In addition, most of them experience neck, back, or shoulder pain (77.8%), fatigue (65.3%), headaches (64.4%), and eyestrain (74.1%). The respondents also complained of joint pain in the fingers and wrists (52.3%) and shoulder pain (60.6%). The majority of the respondents had a high level of knowledge regarding CVS (94.9%) but had a moderate level of awareness regarding CVS (65.7%). As current education and lifestyle are more interrelated to digital device usage, it is recommended that more educational and awareness programmes on CVS be promoted.